Literary theory, negative poetics, and studies in English Literature in the works of Giorgio Manganelli - De Gyurgyokai, Mirko Zilahi (Trinity College (Dublin, Ireland). Italian Department, 2007)
After a brief account of Manganelli's biography, Part One of the dissertation (GIORGIO MANGANELLI) focuses mainly on the developments of the writer's relationship with the "Gruppo 63". The section "TEORIA E POETICHE MANGANELLIANE" proposes an analysis of Manganelli's literary theory through the careful study of the articles and essays included in Il rumore sottile della prosa. The investigation follows the unfolding of Manganelli's text in its internal structure and divisions (Reading, Writing, Reviewing). It introduces a concise scheme of the specific general principles - the nature of language as discussed in "Appunti di teoria letteraria". It concludes with a comprehensive exploration of Manganelli's works (including Salons, Improvvisi per macchina da scrivere, Discorso dell'ombra e dello sternma, Pinocchio, un libro parallelo, Angoscie di stile) which revolve, though in covert ways, around the theoretical tenets analysed in the thesis.
Keywords: Italian Language and Literature, Ph.D.; Ph.D. Trinity College Dublin